2015
DOI: 10.11613/bm.2015.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic utility of saliva as a non-invasive diagnostic fluid: a systematic review

Abstract: This systematic review presents the latest trends in salivary research and its applications in health and disease. Among the large number of analytes present in saliva, many are affected by diverse physiological and pathological conditions. Further, the non-invasive, easy and cost-effective collection methods prompt an interest in evaluating its diagnostic or prognostic utility. Accumulating data over the past two decades indicates towards the possible utility of saliva to monitor overall health, diagnose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(133 citation statements)
references
References 84 publications
1
115
0
6
Order By: Relevance
“…Some studies reported differently [11, 12]. We are aware of the reviews looking at the usefulness of salivary glucose to monitor glycaemia in type 2 diabetes mellitus [13] or non-specified diabetes mellitus [14, 15]. Although all forms of diabetes mellitus are characterised by hyperglycaemia, their aetiology and pathogenesis vary.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported differently [11, 12]. We are aware of the reviews looking at the usefulness of salivary glucose to monitor glycaemia in type 2 diabetes mellitus [13] or non-specified diabetes mellitus [14, 15]. Although all forms of diabetes mellitus are characterised by hyperglycaemia, their aetiology and pathogenesis vary.…”
Section: Introductionmentioning
confidence: 99%
“…The collection of these fluids presents the valuable advantage of being non-invasive (urine, saliva, sweat, tears…) or minimally invasive (blood), allowing for multiple collections and the collection of meaningful amounts for the analyses to be performed. On the other hand, these fluids also present challenges, such as the extremely high dynamic range of plasma or serum, where a dozen of proteins represent more than 90% of the protein content; the more laborious procedure to obtain pure blood cell specimens [81]; or the still not standardized collection of fluids like saliva, sweat or tears [82][83][84].…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%
“…The main functions of saliva are: maintenance of the mucosa, involvement in chewing, mineralization of teeth, control of microorganisms, taste perception and digestion [64]. The flow rate of saliva varies from zero to several millilitres per minute, depending on the emotional state and stimulation [65]. Nasal mucus is a gelatinous fluid produced by mucous membranes in the nasal passages.…”
Section: (B) Saliva and Nasal Mucusmentioning
confidence: 99%